2007
DOI: 10.3758/bf03193316
|View full text |Cite
|
Sign up to set email alerts
|

Coreference and lexical repetition: Mechanisms of discourse integration

Abstract: The use of repeated expressions to establish coreference allows an investigation of the relationship between basic processes of word recognition and higher level language processes that involve the integration of information into a discourse model. In two experiments on reading, we used eye tracking and event-related potentials to examine whether repeated expressions that are coreferential within a local discourse context show the kind of repetition priming that is shown in lists of words. In both experiments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
80
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(99 citation statements)
references
References 55 publications
16
80
2
1
Order By: Relevance
“…However, a number of previous studies using sentence contexts have reported N400 effects of semantic integration difficulty when cloze probability was relatively well-matched [23,24,25,26,67,68,69]. Although in each individual case one might argue that predictability or association was not perfectly controlled, taken together the results lend support to the idea that integration difficulty does modulate the N400 to some extent.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, a number of previous studies using sentence contexts have reported N400 effects of semantic integration difficulty when cloze probability was relatively well-matched [23,24,25,26,67,68,69]. Although in each individual case one might argue that predictability or association was not perfectly controlled, taken together the results lend support to the idea that integration difficulty does modulate the N400 to some extent.…”
Section: Discussionsupporting
confidence: 62%
“…None of these results provided clear evidence that semantic integration processes do not also modulate the N400 independent of memory access processes, and in fact several studies have argued that they do [13,23,24,25,26]. These have motivated multiple generator accounts in which both access and integration processes contribute to the amplitude of the N400 response.…”
Section: The N400 Responsementioning
confidence: 88%
“…an N400), a repeated NP elicits a smaller amplitude similar negativity (Anderson & Holcomb, 2005;Camblin, Ledoux, Boudewyn, Gordon, & Swaab, 2006, for Experiment 2 using rapid serial visual presentation (RSVP), but c.f. Experiment 1 using auditory presentation; Ledoux, Gordon, Camblin, & Swaab, 2007), and a synonym or a bridged NP (i.e. a new but related referent inferentially licensed by the discourse context) elicits a similar negativity with an amplitude somewhere in between (Anderson & Holcomb, 2005;Burkhardt, 2006).…”
Section: Processing the Anaphormentioning
confidence: 97%
“…La première, généralement désignée sous le terme d'antécédent, introduit l'entité dans le texte et la deuxième, l'anaphore, renvoie à l'antécédent ou première mention du référent 2 (Ledoux, Gordon, Camblin, & Swaab, 2007). Exemple 1 : a) Jean joue au ballon dans la cour de récréation et [Jean/il/le jeune homme] marque un joli but ; b) Jean joue au ballon dans la cour de récréation.…”
Section: Définition De La Coréférenceunclassified